Decompression in Chiari Malformation: Clinical, Ocular Motor, Cerebellar, and Vestibular Outcome - Goldschagg, Nicolina; Feil, Katharina; Ihl, Franziska; Krafczyk, Siegbert; Kunz, Mathias; Tonn, Jörg Christian; Strupp, Michael; Peraud, Aurelia (Frontiers in Neurology, 2017)
Background. Treatment of Chiari malformation can include suboccipital decompression with resection of one cerebellar tonsil. Its effects on ocular motor and cerebellar function have not yet been systematically examined. Objective. To investigate whether decompression, including resection of one cerebellar tonsil, leads to ocular motor, vestibular or cerebellar deficits. Patients and Methods. Ten patients with Chiari malformation type 1 were systematically examined before and after (one week and three months) suboccipital decompression with unilateral tonsillectomy. The work-up included a neurological and neuro-ophthalmological examination, vestibular function, posturography and subjective scales. Cerebellar function was evaluated by ataxia rating scales. Results. Decompression led to a major subjective improvement three months after surgery, especially regarding headache (5/5 patients), hyp-/dysesthesia (5/5 patients), ataxia of the upper limbs (4/5 patients) and paresis of the triceps and interosseal muscles (2/2 patients). Ocular motor disturbances before decompression were detected in 50% of the patients. These symptoms improved after surgery, but five patients had new persisting mild ocular motor deficits three months after decompression with unilateral tonsillectomy (i.e. smooth pursuit deficits, horizontally gaze-evoked nystagmus, rebound and downbeat nystagmus) without any subjective complaints. Impaired vestibular (horizontal canal, saccular and utricular) function improved in 5 of 7 patients with impaired function before surgery. Posturographic measurements after surgery did not change significantly. Conclusions. Decompression, including resection of one cerebellar tonsil, leads to an effective relief of patients’ preoperative complaints. It is a safe procedure when performed with the help of intraoperative electrophysiological monitoring, although mild ocular motor dysfunctions were seen in half of the patients, which were fortunately asymptomatic.